2020
DOI: 10.3892/ol.2020.11387
|View full text |Cite
|
Sign up to set email alerts
|

Complex karyotype with cryptic FUS gene rearrangement and deletion of NR3C1 and VPREB1 genes in childhood B‑cell acute lymphoblastic leukemia: A case report

Abstract: B-cell acute lymphoblastic leukemia (B-ALL) is a hematopoietic malignancy characterized by overproduction of immature B-lymphoblasts. BALL is the most common pediatric tumor and remains the leading cause of mortality in children and adolescents. Molecular and cytogenetic analyses of BALL revealed recurrent genetic and structural genomic alterations which are routinely applied for diagnosis, prognosis and choice of treatment regimen. The present case report describes a 4-year-old female diagnosed with BALL. GTG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…For example, B‐ALL characterized by an ETV6 :: RUNX1 rearrangement or hyperdiploidy with double trisomy has an excellent survival rate of 93%, and may be treated with less intensive therapy than other subtypes 17,18 . On the other hand, KMT2A rearrangement, BCR::ABL1 (Philadelphia chromosome) rearrangement (Ph + ), and Philadelphia‐like (Ph‐like, e.g., CRLF2 rearrangement, often with IKZF1 deletion) are among the subtypes associated with less favorable prognoses 19–24 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, B‐ALL characterized by an ETV6 :: RUNX1 rearrangement or hyperdiploidy with double trisomy has an excellent survival rate of 93%, and may be treated with less intensive therapy than other subtypes 17,18 . On the other hand, KMT2A rearrangement, BCR::ABL1 (Philadelphia chromosome) rearrangement (Ph + ), and Philadelphia‐like (Ph‐like, e.g., CRLF2 rearrangement, often with IKZF1 deletion) are among the subtypes associated with less favorable prognoses 19–24 …”
Section: Introductionmentioning
confidence: 99%
“…17,18 On the other hand, KMT2A rearrangement, BCR::ABL1 (Philadelphia chromosome) rearrangement (Ph + ), and Philadelphia-like (Ph-like, e.g., CRLF2 rearrangement, often with IKZF1 deletion) are among the subtypes associated with less favorable prognoses. [19][20][21][22][23][24] We have previously shown that concomitant CRLF2 rearrangement and IKZF1 deletion are associated with H/L ethnicity. 25 In the current study, we sought to identify novel genetic drivers and secondary genetic alterations in B-ALL associated with H/L ethnicity.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly CK in B-ALL is defined with ≥ 5 abnormalities [ 8 ]. CKs have been incorporated into the definition of high-risk ALL and many studies have suggested new definitions based on affected regions or types of aberrations [ 9 , 10 ]. However, their prognostic significance has not been consistently validated in large series.…”
Section: Introductionmentioning
confidence: 99%
“…These genes include a large number of transcription factors and transmembrane receptors, such as Notch1, E2A, CRLF2, EBF1, BTK, JAK2, λ5, BLNK, PIK3R1, IKZF1, PAX5, and VPREB1 10–12. Among them, the association of specific gene alterations and deletions such as IKZF1 and VPREB1 with ALL prognoses has been identified 13,14. The differentiation of precursor BCR (pre-BCR) involves a complex combination of expression of intracellular and cell surface markers with the rearrangement of the immunoglobulin heavy (H) and light (L) chain genes, and association of heavy chain with surrogate light chains (SLC) or pseudo light chain containing VPREB1 and λ5 proteins and signaling subunits Igα and Igβ 15,16.…”
mentioning
confidence: 99%
“…[10][11][12] Among them, the association of specific gene alterations and deletions such as IKZF1 and VPREB1 with ALL prognoses has been identified. 13,14 The differentiation of precursor BCR (pre-BCR) involves a complex combination of expression of intracellular and cell surface markers with the rearrangement of the immunoglobulin heavy (H) and light (L) chain genes, and association of heavy chain with surrogate light chains (SLC) or pseudo light chain containing VPREB1 and λ5 proteins and signaling subunits Igα and Igβ. 15,16 These processes are represented as the first checkpoint in B-cell development.…”
mentioning
confidence: 99%